Dichorionic triplet pregnancies: risk of miscarriage and severe preterm delivery with fetal reduction versus expectant management. Outcomes of a cohort study and systematic review. (8th April 2015) - Morlando, M; Ferrara, L; D'Antonio, F; Lawin‐O'Brien, A; Sankaran, S; Pasupathy, D; Khalil, A; Papageorghiou, A; Kyle, P; Lees, C; Thilaganathan, B; Bhide, A
<x xml:space="preserve">Abstract</x> Background In trichorionic pregnancies, fetal reduction from three to two lowers the risk of severe preterm delivery, but provides no advantage in survival. Similar data for dichorionic triamniotic (DCTA) triplets is not readily available. Objectives To document the natural history of DCTA triplets and the effect of reduction on the risk of miscarriage and severe preterm delivery, compared with expectant management. Search strategy Systematic search on MEDLINE, EMBASE, and the Cochrane Library. Selection criteria DCTA triplets with three live fetuses at 8–14 weeks of gestation, outcome data with expectant management and/or reduction, miscarriage before 24 weeks of gestation and/or severe preterm delivery before 32–33 weeks of gestation. Data collection and analysis Five studies were included. Data from these were combined with data from three centres. Main results There were 331 DCTA triplets. The miscarriage rate was 8.9% (95% CI 5.8–13.3%) and the severe preterm delivery rate was 33.3% (95% CI 27.5–39.7%), with expectant management. The miscarriage rate was 14.5% (95% CI 7.6–26.2%) with a reduction of the monochorionic pair, 8.8% (95% CI 3.0–23.0%) with a reduction of one fetus of the monochorionic pair, and 23.5% (9.6–47.3%) with a reduction of the fetus with a separate placenta. Severe preterm delivery rates were 5.5% (95% CI 1.9–14‐9%), 11.8% (95% CI 4.7–26.6%), and 17.6% (95% CI 6.2–41.0%), respectively. Conclusions In DCTA triplets, expectant management is a reasonable choice when the top priority is a liveborn infant. Where the priority is to minimise severe preterm delivery, the most advisable option is fetal reduction. Further studies are needed to clarify which particular technique is advisable to optimise the outcome.